Effect of Motivation on Employee Work Productivity at PT. Asuransi Takaful Umum - Zahra Nur Azizah; Veithzal Rivai Zainal; Lenny Christina Nawangsari (Dinasti Publisher, 2023)
Every company has an absolute right to be able to achieve the target or mission that has been set, one of which is to increase productivity by optimizing the motivation of human resources in the company concerned. A foundation for the company's success is directed and effective human resources, thus creating an increase in work motivation. Motivation is the encouragement of individuals or groups to carry out a job that has a certain mission. Productivity is the desire of individuals or groups to improve the quality of activities in all fields. This study aims to see the effect of motivation on the work productivity of employees of PT Asuransi Takaful Umum. The study population is the employees of PT Asuransi Takaful Umum. The total study sample is 30 respondents. Data collection uses questionnaires, interviews, and literature studies. This study uses quantitative descriptive analysis and simple linear regression analysis. The results of the study stated that partially the variable of motivation had a significant positive effect on the work productivity of employees of PT Asuransi Takaful Umum. Moreover, simple linear regression states that the motivational variable has a positive effect on the work productivity of employees of PT Asuransi Takaful Umum.